Differential retinoic acid signaling in tumors of long- and short-term glioblastoma survivors - Bărbuş, Sebastian Liviu; Tews, Björn; Karra, Daniela; Hahn, Meinhard; Radlwimmer, Bernhard; Delhomme, Nicolas; Hartmann, Christian; Felsberg, Jörg; Krex, Dietmar; Schmitz-Schackert, Gabriele; Martinez, Ramon; Reifenberger, Guido; et al. (Journal of the National Cancer Institute, 2011)
Although the prognosis of most glioblastoma patients is poor, 3%-5% patients show long-term survival of 36 months or longer after diagnosis. To study the differences in activation of biochemical pathways, we performed mRNA and protein expression analyses of primary glioblastoma tissues from 11 long-term survivors (LTS; overall survival ≥ 36 months) and 12 short-term survivors (STS; overall survival ≤ 6 months). The mRNA expression ratio of the retinoic acid transporters fatty acid-binding protein 5 (FABP5) and cellular retinoic acid-binding protein 2 (CRABP2), which regulate the differential delivery of retinoic acid to either antioncogenic retinoic acid receptors or prooncogenic nuclear receptor peroxisome proliferator-activated receptor delta, was statistically significantly higher in the tumor tissues of STS than those of LTS (median ratio in STS tumors = 3.64, 10th-90th percentile = 1.43-4.54 vs median ratio in LTS tumors = 1.42, 10th-90th percentile = −0.98 to 2.59; P < .001). High FABP5 protein expression in STS tumors was associated with highly proliferating tumor cells and activation of 3-phosphoinositide-dependent protein kinase-1 and v-akt murine thymoma viral oncogene homolog. The data suggest that retinoic acid signaling activates different targets in glioblastomas from LTS and STS. All statistical tests were two-sided.
Gesehen am 17.02.2022